Weather and crime in South Africa - Anna Bruederle; Jörg Peters; Gareth Roberts (RWI - Leibniz-Institut für Wirtschaftsforschung, 2017)
South Africa has one of the highest crime rates in the world, incurring high cost for society. The present paper examines the effect of weather shocks on various types of crime. Using a 12-year panel data set at monthly resolution on the police ward level, we demonstrate a short-term effect of warmer temperatures on violent crime and thereby offer support for the heat-aggression link as suggested by psychological research. Furthermore, we find evidence for a mid-term effect of weather on crime via agricultural income, which is in line with the economic theory of crime. Our findings have direct policy implications for the design of crime prevention strategies, in which weather forecasts could play an important role.
Keywords: C33; O55; Q54; R11; 330; South Africa; weather; crime; income shocks